Perbedaan Pandangan Dalam Pengembangan Ahli Waris Menurut Sunni, Syi’ah Dan Hazairin - Imam Muhardinata (El-Ahli : Jurnal Hukum Keluarga Islam, 2020)
Specifically for Islamic inheritance law in Indonesia, there are several differences among the fuqaha 'which are broadly divided into three groups, namely: first, commonly referred to as Sunni schools which tend to be Patrilineal and secondly Shi'ite schools which tend to be Matrilineic and Hazairin teachings which are tend to be Parental / Bilateral. In the further development of Islamic inheritance law, the Compilation of Islamic Law (KHI) was born, which is an ijma 'sharih in the form of workshops of Ulama and Muslim Scholars throughout Indonesia on 2-5 February 1988, before the issuance of Presidential Instruction No. 1 of 1991 and the Decree of the Minister of Religion No. 154 of 1991, after the existence of the Religious Courts was recognized by the presence of Law No.7 of 1989 concerning Religious Courts. Ijtihad in inheritance law has been practiced since ancient times by Muslims, then what stands out is the Sunni group with the Shiite group. Then in Indonesia Ijtihad this inheritance law was carried out by Hazairin. The main difference between them is the understanding of the position of women in the inheritance legal system. This is because the basic analysis of the development of inheritance law set out in the Koran is different. According to the Sunnis based on the patrilineal system which became a pre-Islamic Arabic culture, while the Shi'a besides that there is a principle based on the interests of women, so that the position of men and women are equal. Whereas Hazairin on the basis of a bilateral or parental system based on the principle of the position of men and women are the same, so that the views of Shi'a and Hazairin are not much different.